2008
DOI: 10.1021/pr800359d
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Proteome Analysis of Transgenic Plants Expressing Antiviral Antibodies

Abstract: The expression of exogenous antibodies in plant is an effective strategy to confer protection against viral infection or to produce molecules with pharmaceutical interest. However, the acceptance of the transgenic technology to obtain self-protecting plants depends on the assessment of their substantial equivalence compared to non-modified crops with an established history of safe use. In fact, the possibility exists that the introduction of transgenes in plants may alter expression of endogenous genes and/or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 64 publications
4
42
0
Order By: Relevance
“…Samples were prepared according to Tsugita and Kamo (1999) with some modifications (Di Carli et al, 2009). Extracted proteins were purified using the Clean-Up kit (GE Healthcare) and quantified using the DC Protein Assay (Bio-Rad).…”
Section: Proteome Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Samples were prepared according to Tsugita and Kamo (1999) with some modifications (Di Carli et al, 2009). Extracted proteins were purified using the Clean-Up kit (GE Healthcare) and quantified using the DC Protein Assay (Bio-Rad).…”
Section: Proteome Analysismentioning
confidence: 99%
“…Two-dimensional gel electrophoresis was carried out using the GE Healthcare DIGE system. Purified proteomes were covalently labeled using the CyDye DIGE Fluor (Cy2, Cy3, and Cy5) according to the manufacturer's instructions and analysis carried out as described previously (Di Carli et al, 2009). A random design with 12 gels and a dye-swap approach was used to avoid labeling artifacts and ensure statistical significance.…”
Section: Proteome Analysismentioning
confidence: 99%
“…In another study, the expression of recombinant antibodies in two transgenic crops (tomato and tobacco)-as a strategy to confer self-protection against virus attack-did not significantly alter the leaf-proteome profile (Di Carli et al, 2009). However, Rocco et al (2008) observed that a tobacco transformed with the tomato prosystemin gene affected the expression of a number of proteins involved in FIGURE 1.…”
Section: A Ms-based Approaches For Proteomic Profilingmentioning
confidence: 98%
“…2-DGE provides the highest protein-resolution capacity with a low-instrumentation cost. This technique has been applied to compare protein profiles of GMOs, including wheat with improved functional properties (Di Luccia et al, 2005;Scossa et al, 2008), tomatoes with a genetically added resistance to virus and insect attacks (Corpillo et al, 2004;Di Carli et al, 2009), potatoes showing modified cell wall structure and a delayed sprouting process (Careri et al, 2003;Lehesrant et al, 2005) and insect-resistant GM maize (Albo et al, 2007;Zolla et al, 2008;Coll et al, 2011;Balsamo et al, 2011) versus their corresponding unmodified lines. The comparison of protein profiles of GMOs with those obtained from the unmodified lines often does not reveal more significant differences than those observed between different nonmodified cultivars/genotypes.…”
Section: Ms-based Protein Profilingmentioning
confidence: 99%